Video Games Take Testing to the Next Level. - ROTHMAN, ROBERT (Education Digest, 2011)
The article presents a condensed reprint of the article "Video Games Take Testing to the Next Level," by Robert Rothman, which appeared in the December 2010 issue of "Harvard Education Letter." It discusses the use of video games to assess students in areas such as problem-solving ability and the conduct of scientific inquiry. A model of student assessment that involves the use of video games, which was developed by literacy professor James Paul Gee and colleagues, is addressed.